Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah BKK Dengan Kepuasan Sebagai Variabel Intervening - Mulyono, Ernawati & (Eksplorasi, 2011)
ABSTRACTPD BKK Gondangrejo karanganyar a banking service providers, it is no wonder if the PD BKK Gondangrejo karanganyar while respecting the quality of the services at this institution, because we know that the survival and success of service companies such as banking services to customera in an effort to improve customers satisfaction in improving customer loyalty.